The Correlation of Screen Time with Social Emotional Development in Preschool Children Age 4-6 Years - Denisa Adella; Windy Rakhmawati; Imas Rafiyah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Children's involvement with digital devices is something that cannot be avoided in the current technological era, especially because of children's extraordinary curiosity, which indirectly accustoms them to living a sedentary lifestyle (screen time). However, there are undesirable consequences of prolonged and age-inappropriate screen use, which is of concern to developmental experts because it is one of the causes of various health, growth and development problems, as well as behavioral and cognitive problems in children. Objective to determine the correlation between screen time and the social emotional development of children aged 4-6 years. This study used a cross sectional approach with a total sampling technique in classes A and B, totaling 44 children. The questionnaire used is screen time modified by Maulodin (2018) and ASQ SE 2 by Risna (2022) which have been tested for validity and reliability. There is no correlation between screen time and social emotional development with a significance value of 0.111 (p-value > 0.05). Based on majority data, 22 children (50.0%) with high screen time use have appropriate social emotional development. This study concludes that there is no correlation between screen time and social emotional development in preschool children aged 4-6 years. Parents need to pay attention, although screen time is not the only factor that can influence social emotional development in preschool children, but it has the potential to have a negative impact. Parents can teach creative learning methods that can stimulate children's ability to use everyday objects so that children do not spend their time playing with gadgets and can balance the potential negative impact of screen time.